2020
DOI: 10.1287/opre.2019.1950
|View full text |Cite
|
Sign up to set email alerts
|

Information Disclosure and Pricing Policies for Sales of Network Goods

Abstract: Amazon and Apple, which sell tablet devices, have adopted different implicit information policies and developed distinct “reputations” about their tablets’ sales volume release. With Amazon, “even a number as basic, and presumably impressive, as how many Kindle e-readers the company sells is never released.” With Apple, iPhone and iPad sales numbers are always released, even if they are disappointing. In the paper “Information Disclosure and Pricing Policies for Sales of Network Goods,” the authors study the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Markopoulos and Hosanagar ( 2018 ) introduced a game theory model of the competitive market and found that the information availability of the third parties makes companies free-rider, especially low-quality enterprises, who can reduce investment more than high-quality enterprises in information disclosure. Hu et al ( 2020 ) studied a two-phase model, where the sales volume of the first phase is disclosed, based on which the customers of the second phase will make a purchasing decision. The above studies are all focused on disclosing information by the seller to the consumer, while, there are, of course, also studies by the consumer to the seller (Feri et al, 2016 ; Ichihashi, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Markopoulos and Hosanagar ( 2018 ) introduced a game theory model of the competitive market and found that the information availability of the third parties makes companies free-rider, especially low-quality enterprises, who can reduce investment more than high-quality enterprises in information disclosure. Hu et al ( 2020 ) studied a two-phase model, where the sales volume of the first phase is disclosed, based on which the customers of the second phase will make a purchasing decision. The above studies are all focused on disclosing information by the seller to the consumer, while, there are, of course, also studies by the consumer to the seller (Feri et al, 2016 ; Ichihashi, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another stream of related literature is group buying. Hu et al (2020) considered a positive network externality among customers in a general form, which includes group buying as a special case, and show that it may not be optimal for the firm to disclose the number of sign-ups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, a pioneering study by Parakhonyak and Vikander [19] proves that to best exploit network effects, firms should release preorder and sales information to consumers for network goods. Hu et al [8] also studied the sales volume disclosure and pricing problems associated with network goods. e authors systematically analyzed the positive and negative effects of sales disclosure.…”
Section: Related Literaturementioning
confidence: 99%
“…Given the possible positive or negative effect of sales disclosure, we often observe in practice that some firms tend to commit to disclosing sales information, while others never release details. For example, Apple always releases iPhone and iPad sales volumes, but Amazon never announces the number of sales of Kindle products [8]. Recently, Huawei and Xiaomi, competitors in the 5G mobile phone market, successively released the sales quantities of their 5G mobile phones [9].…”
Section: Introductionmentioning
confidence: 99%